Implementation of A QR-Coded Model for Stakeholders and Managers of Traditional People's Markets - Darwis, Darwis; Dihamri, Dihamri; Linda, Linda; Sumaryono, Dino (Poltekkes Kemenkes Palu, 2024)
Health education for market residents to change behavior to create a healthy market can be done using pocketbooks, videos, and posters as the model chosen to create a healthy people's market. Socialization to stakeholders in each market is essential in making this happen. This research aims to determine the delivery mechanism, media either through barcode scans, so that stakeholders can easily convey the source of healthy market messages to traders and buyers to change the habits of market residents which originates from pocketbooks, videos, and posters, to stakeholders, including market managers, to be passed on to traders and buyers or visitors. This research used a qualitative descriptive method focusing on media delivery via QR Barcodes (pocketbooks, videos, and posters). The population in this study are stakeholders related to market management and cleanliness. The sample in this study used a quota sampling technique of 22 people, data collection used focus group discussion (FGD), and qualitative data analysis. The message delivery mechanism by implementing QR Barcodes can make it easier for stakeholders to convey healthy market messages to market residents. Traders want to create a healthy market by participating in spreading information about healthy markets through QR Barcodes. Respondents' most preferred medium for disseminating information is via WhatsApp social media, although suggestion boxes are still one way to channel complaints regarding obstacles in accessing healthy market information.